Obstetrics And Gynecology Residents’ Satisfaction And Selfconfidence After An Anal Sphincter Injury Simulation-Based Workshop In Indonesia: A Pre- And Post-Intervention Comparison Study - Riska Wahyuningtyas, Riska
Abstract Purpose: Obstetric anal sphincter injury (OASI) is one of the most common complication during delivery. Simulation models using manikin can be used as an effective medical learning method to improve students' abilities before meeting patients. It aimed to describe the development of anal sphincter injury model and assess the resident satisfaction and self-confidence after perineal repair workshop with anal sphincter injury simulator in Indonesia.